Análise do processo de elaboração e implementação do novo regimento interno do sistema de bibliotecas da Universidade Federal da Paraíba. - Sousa Filho, Antonio Genésio de (2013)
This study analyzes the process of elaboration and implementation of Internal Regulation that rules the Paraiba Federal University Library System, which was approved by this University s Governing Board, in 2009. The methodological approach consisted of both explanatory and descriptive case study based on nonprobable, intentional sample, consisting of seventeen unit of information managers of the mentioned System. One obtained research data from primary and secondary sources, through structured interviews and documental analysis, respectively. The analysis of data collected during the interviews was performed according to the technique of content analysis which rose evidence of the barriers that might be influencing the implementation process of the new system structure. Moreover, one identified likely deviations in certain administrative procedures related to the elaboration of the herein object of study. The results demonstrate the need of creating an appropriate context for Knowledge Management, primarily through a review in the organizational structure, so that it will foster both integrated and systemic initiatives which might encourage participation and commitment of individuals involved in the activities of the system. Among the organizational guidelines to mitigate the barriers that hinder the implementation of the Internal Regiment of this Library System, one proposes: institutionalization of participation in decision-making; development of a systematic and integrated plan for upgrading the communication system; resizing of the staff; employment of librarians and library assistants; investment in preparation of personnel to occupy management positions; creating an advisory intermediary service, linked to this Library System Office, in order to technically coordinate, and supervise Cross-sector Libraries; establishment of proper salaried department office managers to those who are responsible for the Cross-sector Libraries; development of studies focusing on the continuous improvement of administrative procedures; and creating of a programme of internal marketing. It also recommends the development of a new document regimental, so this will be in accordance to the legal framework that regulates the formation of normative acts.